The taste of mango [videorecording (DVD)] - Seneviratne, Suren (Oscilloscope Laboratories, 2025)
The filmmaker explores the dynamic that exists between her mother, grandmother, and herself resulting from the sexual abuse of her mother in her native Sri Lanka by her mother's stepfather.